Microglia activation in the midbrain of the human neonate: the effect of perinatal hypoxic-ischemic injury - Panayotacopoulou, Maria; Papageorgiou, Ismini; Pagida, Marianna; Katsogridaki, Alexandra E; Chrysanthou-Piterou, Margarita; Valous, Nektarios A.; Halama, Niels; Patsouris, Efstratios; Konstantinidou, Anastasia E (Journal of neuropathology and experimental neurology, 2022)
Perinatal hypoxia-ischemia (PHI) is a major risk factor for the development of neuropsychiatric deficits later in life. We previously reported that after prolonged PHI, the dopaminergic neurons of the human neonate showed a dramatic reduction of tyrosine hydroxylase (TH) in the substantia nigra, without important signs of neuronal degeneration despite the significant reduction in their cell size. Since microglia activation could precede neuronal death, we now investigated 2 microglia activation markers, ionized calcium-binding adapter molecule 1 (Iba1), and the phagocytosis marker Cd68. The highest Iba1 immunoreactivity was found in neonates with neuropathological lesions of severe/abrupt PHI, while the lowest in subjects with moderate/prolonged or older PHI. Subjects with very severe/prolonged or chronic PHI showed an increased Iba1 expression and very activated microglial morphology. Heavy attachment of microglia on TH neurons and remarkable expression of Cd68 were also observed indicating phagocytosis in this group. Females appear to express more Iba1 than males, suggesting a gender difference in microglia maturation and immune reactivity after PHI insult. PHI-induced microglial “priming” during the sensitive for brain development perinatal/neonatal period, in combination with genetic or other epigenetic factors, could predispose the survivors to neuropsychiatric disorders later in life, possibly through a sexually dimorphic way.